Improving the quality of treatment of patients who are in chronic social stress - Makhlynets, Н. П.; Ozhohan, З. Р.; Piuryk, М. В. (Actual Dentistry, 2022)
The aim of the study. Improving the effectiveness of comprehensive treatment of patients with pathological occlusion and existing bad habits through orthodontic treatment and elimination of bad habits. Research methods. 30 patients aged 9–12 years with dental and maxillary anomalies and disorders of the architecture of the oropharynx against the background of bad habits were examined and treated. Patients of group I (15 people) underwent rehabilitation of the oral cavity, orthodontic treatment with removableand non-removable structures, frenuloplasty, and in the postoperative period were prescribed chlorhexidine-dent, patients of group II (15 people) treatment was supplemented with dioxisol (UA/8021/01/01). Conducted a clinical study, where the main point was the detection of abnormally attached frenulum of the lips and tongue, the presence of connective tissue strands in the lateral group of teeth, changes in the dental-maxillary system due to bad habits. X-ray examination (computed tomography, orthopantomography) was used to detect changes in the position of the teeth and their rudiments, density and thickness of the bone structure of the jaw bones. McNamara’s cephalometric parameters were studied, and the thickness of the masticatory muscles was analyzed. We compared the changes in the position of the teeth on models and the indicators of the photoprotocol before treatment, after treatment. All patients underwent a secret questionnaire before and during treatment to identify stressors that affect the body, studied the relationship between the presence of stressors and bad habits in children. Scientific novelty. Clinical studies have shown that 90 % of patients surveyed (27 people) have bad habits that are associated with chronic social stress. Patients who were able to overcome the bad habit were more likely to receive the desired therapeutic effect from the treatment based on the results of clinical and radiological examination, cephalometric analysis and photoprotocol. All patients before treatment had violations of the architecture of the oropharynx, which were manifested by highly attached strands in the area of the canines, premolars and frenulum of the lip on the lower jaw (less than 5 mm); low-attached strands in the area of the canines, premolars and frenulum of the lip on the upper jaw (less than 5 mm). In patients whose dioxyzole was included in the surgical correction of architectural disorders, the formation of a normotrophic scar was observed, which did not cause a traumatic effect on periodontal tissues and the position of a particular group of teeth. In patients who included dioxysol in the complex treatment, the formation of a normotrophic scar was observed, which did not cause traumatic effects on periodontal tissues and the position of a particular group of teeth. Computed tomography data showed changes in the density and thickness of the bone structure of the jaw bones in areas where they were able to eliminate the bad habit. Evaluation of models of dentition after treatment confirmed the radiological characteristics. Conclusions. Bad habits progress in the presence of chronic social stress, which according to the survey, is manifested in 90 % of patients. Frenuloplasty is an important stage in the complex treatment of patients with dental and maxillary anomalies and the presence of anomalies in the architecture of the dorsum of the mouth. After active orthodontic treatment with removable and non-removable structures and conduction, frenuloplasty, constant struggle over chronic habits and leveling of stress factors by eliminating stressors, we get the desired therapeutic effect in orthodontic patients.